116k views
3 votes
AC = 23. AB = 2x + 2, and BC = 3x + 6. Find BC ​

1 Answer

2 votes

Answer:

21

Explanation:

Given AC = 23, AB = 2x + 2 and BC = 3x+6 then using vector notation;

BA+AC = BC

Since BA = -AB

The equation becomes -AB+AC = BC

Substituting the given equations;

-(2x+2)+23 = 3x+6

open the parenthesis

-2x-2+23 = 3x+6

-2x+21 = 3x+6

collect the like terms

-2x-3x = 6 - 21

-5x = -15

Divide both sides by -5

-5x/-5 = -15/-5

x = 3

TO get BC, we will substitute x = 3 into the expression BC = 3x+6

BC = 3(5)+6

BC = 15+6

BC = 21

Hence the length of BC is 21 units

User Jonju
by
5.0k points